Cytogenetic comparison of Cuscuta psorothamnensis and C. veatchii (Convolvulaceae), two species originated from recurrent hybridization between the same diploid parents - Moura Ibiapino, Amalia (2024)
Fil: Moura Ibiapino, Amalia. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.